Society's Awareness of the Role of Radiation in Early Detection of Breast Cancer - Elgadaime, Adnan A. Frag; Eljamay, Salwa Muftah (CV. Literasi Indonesia, 2024)
This research aims to know society's awareness of the role of radiation in the early detection of breast cancer. The questionnaire was compiled by Google Form the English-language version of the questionnaire. The first set included 3 (sex, age, education,). Followed by a set of 11 questions regarding knowledge. Result: Age Groups: The participants' ages ranged from 15 to 75, with the majority (20.9%) in the 36-40 years category. Most respondents were female (78.2%), with males representing 21.8% of the sample. Highest Representation: University graduates (43.2%) formed the largest educational group. Others: Master's holders (11.8%) and individuals from high institutes (15.9%) also had significant representation. Breast Cancer Screening Awareness: 72.3% of respondents were aware of the importance of breast cancer screening. Visits for Screening: Only 14.5% of participants reported visiting a clinic for breast cancer screening, while 83.2% had not. Awareness of Radiation Usage: Nearly half (47.7%) were aware that radiation is used in early breast cancer detection, and 38.6% knew it could also be used for treatment. Knowledge of Dosage Risks: 46.8% recognized that high radiation doses could increase cancer risk. Preferred Methods for Breast Cancer Detection: Best Method: The most commonly preferred option for breast cancer detection was “All the above” (31.4%), encompassing clinical examination, self-inspection, radiation inspection, and medical analysis. The findings indicate a widespread awareness of breast cancer screening; however, they also reveal significant gaps in participation rates and a limited understanding of the associated risks and benefits of radiation.